Effect Of Squat Jump And Jump To Box Exercises On The Ability Of The Long Jump Without A Start On Teenage Star Athletic Club Athletes Tanah Pinem District Dairi District In 2023 - Prima, Asep; Sembiring, Walmar Haganta; Amansyah, Amansyah; Arima, Putra (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to determine the effect of squat jump and jump-to-box training on the long jump ability without starting in athletes at the Bintang Teen athletics club, Tanah Pinem sub-district, Dairi district in 2023. There is a problem among athletes at the Bintang Teen Athletics Club who lack long jump results, training methods and performance in athletes. This research was conducted on Jalan Pendidikan, Tanah Pinem District, Dairi Regency with a population of 13 people and a sample of 10 people. The method used in this research is quantitative, experimental-based with a pre-test (pre-test) and research instruments by testing the athlete’s jump results measuring them and then recording them. There are two training programs where both forms of training are designed to improve long jump ability in athletics. The benefit of this research is to provide information about the importance of squat jump and jump-to-box training to improve long jump ability. Then the samples were given treatment in the form of a training program with variations of passing exercises. With a training program prepared, then after 6 weeks of undergoing the training program, the sample takes a final test (post-test). The pre-test and final test were taken using the long jump test instrument without a prefix, Rama Setya 2022. Data analysis technique or hypothesis analysis, namely, the effect of squat jump and jump-to-box training on the long jump ability of athletes at the Bintang Teen athletic club, Tanah Pinem District, Dairi Regency, the Year 2023, it is obtained that tcount = 10.19 > ttable = 2.26 at the real level α = 0.05 then tcount > ttable. Based on the hypothesis testing criteria, namely H0 is rejected and Ha is accepted, this research states that “there is a significant training effect from the squat jump and jump to box training on long jump ability without starting in athletes at the Bintang Teen athletic club, Tanah Pinem sub-district, Dairi district in 2023 ”.